Recent progresses in the adsorption of organic, inorganic, and gas compounds by MCM-41-based mesoporous materials - Costa, José Arnaldo S.; de Jesus, Roberta A.; Santos, Danilo O.; Mano, João F.; Romão, Luciane P.C. [UNESP]; Paranhos, Caio M. (Elsevier, 2020)
Adsorbent mesoporous materials are highly efficient for the remediation of different compounds in environmental applications such as organic, inorganic, and gas molecules. These compounds are removed by the traditional adsorption process in batch assessments. In this review, we report the recent progress on the MCM-41-based mesoporous material syntheses and its strategic use as an adsorbent material for the removal of different pollutants. Also approached the main factors that affect its synthesis and the methods of functionalization most used to prepare the MCM-41-based functionalized mesoporous materials. On the other hand, the factors that affect the adsorption process were also investigated. In addition, it is possible to affirm that adsorption technology has attracted a lot of attention in the removal of environmental pollutants, mainly due to the fact that it is a technique that requires the use of few steps and equipment, easy operation, low cost, does not generate residues or by-products, eco-friendly, and high energy efficiency, which allow its wide application on the remediation processes.
Keywords: Adsorption process; Environmental remediation; MCM-41; Mesoporous material; Pollutants